ANALISIS PENINGKATAN KEMAMPUAN LITERASI SAINS SISWA: SEBUAH STUDY METASSYNTESIS - Maulana, Riswandi; Abidin, Zaenal (PGSD Universitas Muhammadiyah Cirebon, 2023)
Abstract Scientific literacy is the ability to be involved with issues related to science, and various scientific ideas, as a reflective citizen, so the assessment of scientific literacy is not merely a measurement of the level of understanding of scientific knowledge but also an understanding of various aspects of the scientific process and the ability to apply knowledge and scientific processes in real situations faced by students. The literature search was carried out on the ERIC electronic database with the keyword